Análise do ciclo de vida de cenários para o tratamento de resíduos sólidos urbanos na região metropolitana de Fortaleza/Ce, Brasil: tecnologia WASTE-TO-ENERGY - Lima, Auceliane André da Silva (2024)
Solid waste management poses a significant challenge for developing countries, such as Brazil, and is particularly critical in the Northeast region. In this context, this thesis investigates sustainable waste management solutions in Fortaleza, one of the largest cities in the Northeast region, analyzing the life cycle and considering waste-to-energy technologies, focusing on mechanical treatment for the selection of recyclables and the production of RDF (Refuse- Derived Fuel). Structured in three chapters, the thesis discusses a literature review based on scientific articles and technical reports from government bodies about the potential for RDF production and its co-processing in the cement industry, covering global and national aspects, in addition to addressing the perspective of solid waste management in Brazil. The second chapter contemplates life cycle analysis (LCA), conducted with the openLCA software and the ecoinvent database, adapting the model to the Brazilian context with specific local information. Five scenarios for the treatment of municipal solid waste from the city's household collection were analyzed. Scenario C1 (considered the baseline scenario) represents the current municipal solid waste management system in Fortaleza via treatment in a sanitary landfill with biogas recovery. Scenario C2 is similar to scenario C1, its differential being the inclusion of mechanical treatment for the separation of recyclables and production of RDF that is sent to the cement industry, scenario C3 contemplates the incineration of waste for the generation of electricity, scenario C4 is similar to scenario C2 with the difference that the RDF is sent for incineration for energy generation instead of use in the cement industry; scenario C5 contemplates the treatment of waste in a sanitary landfill, however without the biogas recovery system. The evaluation of the results indicates that scenario C2 is the most favorable, presenting greater environmental credit. Even when analyzing sub-scenarios with different rates of recyclables and RDF, we observe lower impacts compared to the current scenario. The comparison of scenarios C2 and C4 indicates that the use of RDF as an alternative fuel in the cement industry has a lesser impact on the climate change category than its use for electric energy generation through incineration. The comparison between scenarios C1 and C5 indicates that with the implementation of the biogas capture system in the landfill, there is a reduction of about 40% in CO2-Eq emissions, however, other indicators showed higher environmental burdens, which demonstrates that this practice alone is not sufficient to achieve truly sustainable waste management. On the other hand, financial indicators, such as the internal rate of return and net present value, indicate that the economic viability of mechanical treatment strongly depends on high volumes of recyclable materials. In this study, the cost of acquiring the technological equipment, estimated from a German company, represents the largest share of the total investment.